Crecimiento de indicadores económicos y su relación con la recaudación de los impuestos en la Municipalidad Provincial de San Martín 2009-2013 - Alburqueque Cenepo, Susana Karola (2015)
This research titled: Growing economic indicators and their relation to the collection of taxes in the provincial municipality of San Martin 2009-2013, has the general objective to establish the relationship of economic growth indicators and the collection of taxes in provincial municipality of San Martin. During the investigation we worked with a type of descriptive and correlational research, with a level of quantitative research; working for it with a sample population to the Provincial Municipality of San Martin, obtaining information from the periods 2009, 2010, 2011, 2012 and 2013; thereby making use of the technique of document analysis and instrument sheets document analysis. Later, with the information processing it proceeded to resolve according to the objectives; the result being that there is a similar trend among the collection of municipal taxes and the growth of economic indicators, ie, both variables have been increasing gradually, so you can say Hi: Growth of economic indicators is related to the collection duty of the provincial municipality of San Martin in the periods 2009 to 2013.